Analysis of Microwave and Optical Devices by Using Quasi-TEM Finite Element Technique - Zareen, Ismat; Alam, M. Shah; Amin, Mahbub (Journal of Electrical Engineering, 2012)
The quasi-TEM finite element analysis of microwave and optical devices has been carried out in this work. The static approach that involves the solution of Laplaces equation can be utilized to characterize many important properties of microstrip lines, microshield lines, and microwave photonic components. In this work, we have incorporated such an analysis to obtain propagation loss in MMIC transmission lines and high-speed electrooptic modulators on LiNbO3 and GaAs. It is shown that microwave losses play an important role on optical bandwidth of these modulators and the estimation of bandwidth depends on accurate calculation of loss. Here, the Perlows generalized equation has been used to estimate the propagation loss of MMIC lines and very good agreement with the previously published results has been obtained. Very important microwave properties for the design and optimization of MMIC lines and modulators, such as, microwave effective index, characteristic impedance are also calculated by using the capacitance per unit length. These properties have been used in the estimation loss. The dependence of microwave properties with the structural parameters are also investigated and it has been found that considering a dielectric material lossless always lead to an over estimation of optical bandwidth of modulators. Journal of Electrical Engineering The Institution of Engineers, Bangladesh Vol. EE 37, No. II, December, 2011